Comparing European and U.S. Securities Regulations : MiFID versus Corresponding U.S. Regulations - Boskovic, Tanja; Cerruti, Caroline; Noel, Michel (Washington, DC: World Bank, 2013)
The purpose of this paper is to compare the European Union (EU) and United States (U.S.) securities regulations. In November 2007, the market in financial instruments directive 2004/39/EC (MiFID) came into force in the EU, and brought about deep changes in the market infrastructure. The same year regulations National Market System (NMS) in the U.S. was fully enacted and reformed equities markets. This study compares MiFID with the corresponding U.S. regulations, and primarily focuses on the regulatory and supervisory framework, trading venues, and the provision of investment services. Implementation of the rules enforcement and right to redress are beyond the scope of this paper. Likewise, the paper does not intend to judge the effectiveness of the two regulatory systems.